The Analgesic and Anti-Inflammatory Activity of in Balb/c Mice - Mahmoud Rafieian-kopaei PhD; Abdollah Shakiba MD; Mehrnoosh Sedighi PhD Cand; Mahmoud Bahmani PhD Cand (SAGE Publishing, 2017)
Linum usitatissimum L is traditionally used for relief of pain and inflammation. In this study, the analgesic and anti-inflammatory effects of this plant were evaluated. Xylene test was used for anti-inflammatory evaluation in which 48 mice were randomly designated into 6 groups of 8 each including: control, dexamethasone as positive control (15 mg/kg), and experimental groups (42, 85, 170, and 340 mg/kg, respectively). For analgesic evaluation, 192 mice were randomly designated into 4 sets of 6 groups of 8 mice, including control, morphine as positive control, morphine plus naloxone, experimental groups (200 and 500 mg/kg extract), and extract along with naloxone group, which received 500 mg/kg. The analgesic activities were evaluated at 5, 15, 30, and 60 minutes, respectively, in each set. Both doses showed analgesic activity, the 200 mg/kg possessed higher effects ( P < .05). Naloxone reduced a section of its effect ( P < .001). The 170 mg/kg dose of the extract showed anti-inflammatory activity ( P < .05). The extract had phenolic, flavonoid, and flavonol compounds with antioxidant activity. Linum usitatissimum L dose dependently had analgesic activity partially like morphine and might be used as analgesic and anti-inflammatory agent.